2016
DOI: 10.1007/s12016-016-8529-8
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the Immune System with Skin and Bone Tissue in Psoriatic Arthritis: A Comprehensive Review

Abstract: Cutaneous psoriasis [e.g. psoriasis vulgaris (PsV)] and psoriatic arthritis (PsA) are complex heterogeneous diseases thought to have similar pathophysiology. The soluble and cellular mediators of these closely related diseases are being elucidated through genetic approaches such as genome-wide association studies (GWAS), as well as animal and molecular models. Novel therapeutics targeting these mediators (IL-12, IL-23, IL-17, IL-17 receptor, TNF) are effective in treating both the skin and joint manifestations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 121 publications
0
25
0
4
Order By: Relevance
“…As presented below, TNIP1 is an oft-cited gene in GWAS studies with SNPs in certain populations suffering from systemic lupus erythematosus, psoriasis, and systemic sclerosis [ 13 16 ]. For recent consideration of possible genetic association of TNIP1 with other autoimmune diseases such as Sjögren syndrome and psoriatic arthritis, the reader is directed to [ 82 , 83 ].…”
Section: Tnip1 In Inflammation and Diseasementioning
confidence: 99%
“…As presented below, TNIP1 is an oft-cited gene in GWAS studies with SNPs in certain populations suffering from systemic lupus erythematosus, psoriasis, and systemic sclerosis [ 13 16 ]. For recent consideration of possible genetic association of TNIP1 with other autoimmune diseases such as Sjögren syndrome and psoriatic arthritis, the reader is directed to [ 82 , 83 ].…”
Section: Tnip1 In Inflammation and Diseasementioning
confidence: 99%
“…[48] The pathogenesis of PsA is not fully understood; however, findings from several studies suggest that IL-17 plays a role in disease development and progression, including genomewide association studies showing a link to IL-23/Th17 mediators such as IL-12B and IL-23R. [49] Using flow cytometry and Western blot analyses, Raychaudhuri and colleagues found that PsA-isolated synoviocytes have higher IL-17A receptor (IL-17RA) [50] levels than synoviocytes from patients with osteoarthritis and that the synovial fluid of patients with PsA has significantly higher levels of Th17 cells that produce functionally active IL-17 and that, in turn, induces upregulation of IL-6, IL-8 and MMP-3. Furthermore, in animal models of collageninduced arthritis, disruption of IL-17 signalling (IL-17-deficient mice and an anti-IL-17 antibody) protects against bone resorption.…”
Section: Psoriatic Arthritismentioning
confidence: 99%
“…The IL-23/IL-17 axis is also involved in the pathogenicity of PsA [ 46 ]. In addition to AS, polymorphisms in IL23R are a risk factor for PsA [ 47 ].…”
Section: Il-23 and Inflammatory Arthritismentioning
confidence: 99%